German public opinion on admitting refugees - Jürgen Gerhards; Silke Hans; Jürgen Schupp (DIW Economic Bulletin, 2016)
Since the beginning of 2016, the Socio-Economic Panel (SOEP) study has been conducting a monthly survey of German attitudes, expectations, and fears concerning migration. The third wave of the survey,-the Barometer of Public Opinion on Refugees in Germany (Stimmungsbarometer zu Geflüchteten in Deutschland)-, conductedin March 2016, shows that more than half of all respondents still associate the influx of refugees with more risks than opportunities. Nonetheless, a clear majority (81 percent of respondents) are in favor of admitting refugees and those fleeing political persecution, in accordance with international law. At the same time, however, the majority are of the conviction that refugees should be sent back to their home country once their reason for leaving it no longer pertains. Only 28 percent of all respondents are in favor of allowing refugees who have already been living in Germany for some time to remain in the country even after the situation in their country of origin has improved.
Keywords: A13; D64; I31; 330; refugees; asylum seekers; public opinion